Photocalytic Coatings for Air-Purifying, Self-Cleaning and Antimicrobial Properties (MDPI - Multidisciplinary Digital Publishing Institute, 2015)
This Special Issue of Coatings is focused on the study of different photocatalyst-based coatings for developing self-cleaning, air-purifying and antibacterial properties. In this case, a wide variety of photocatalysts (TiO2, Si-TiO2, TiO2−xNy, Ag-TiO2, Mo-TiO2, ZnO, SnO2-Ag, Nb2O5 and C60 fullerene) were evaluated towards the removal of different molecules. Similarly, substrates such as glass, silica, sapphire, polycarbonate, aluminium, stainless steel, concrete and mortar were included in this issue. This information certainly contributes to a better understanding of the photocatalytic removal of different molecules (e.g., Escherichia coli, Staphylococcus aureus, resazuring, rhodamine B, methylene blue, Demeton-S, 2-chloroethyl phenyl sulfide (CEPS) and NOx (NO and NO2)) and the coating technologies required for such performances. Based on these interesting results, I encourage you to read through this Special Issue and use the valuable information provided therein to help us move forward in the exciting area of photocatalytic coatings for developing air-purifying, self-cleaning, and antimicrobial properties.